2015
DOI: 10.1039/c4sc03613a
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting parameter space in MOFs: a 20-fold enhancement of phosphate-ester hydrolysis with UiO-66-NH2

Abstract: Using the enzymatic mechanism of phosphoesterase as a template, we were able to modify a metal–organic framework such that the hydrolysis rates were 50 times faster than previously demonstrated with UiO-66.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
273
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 282 publications
(301 citation statements)
references
References 74 publications
13
273
1
Order By: Relevance
“…We hypothesized that this synergy would result in enhanced catalytic activity towards phosphate ester bond hydrolysis since the phosphotriesterase enzyme that performs this reaction in nature also contains a Lewis acidic active site with a proximal base. In addition to the promising activity demonstrated by UiO‐66 and its amino functionalized derivative, we have also shown that using UiO‐67 (Figure ), a MOF which is isostructural to UiO‐66 but contains 4,4′‐biphenyldicarboxylic acid linkers and larger pores, results in a further enhancement in hydrolysis reaction rate compared to UiO‐66 (Figure and Table ) . This reaction rate enhancement is to be expected given that diffusion of the simulant DMNP in UiO‐67 is expected to be faster compared to that in UiO‐66 .…”
Section: Figurementioning
confidence: 72%
See 1 more Smart Citation
“…We hypothesized that this synergy would result in enhanced catalytic activity towards phosphate ester bond hydrolysis since the phosphotriesterase enzyme that performs this reaction in nature also contains a Lewis acidic active site with a proximal base. In addition to the promising activity demonstrated by UiO‐66 and its amino functionalized derivative, we have also shown that using UiO‐67 (Figure ), a MOF which is isostructural to UiO‐66 but contains 4,4′‐biphenyldicarboxylic acid linkers and larger pores, results in a further enhancement in hydrolysis reaction rate compared to UiO‐66 (Figure and Table ) . This reaction rate enhancement is to be expected given that diffusion of the simulant DMNP in UiO‐67 is expected to be faster compared to that in UiO‐66 .…”
Section: Figurementioning
confidence: 72%
“…Among the linker‐appended functional groups screened, primary amine bearing MOFs have shown unprecedented activity in the hydrolysis of DMNP. We have demonstrated that, while keeping other factors constant, installing a primary amine group on the benzene‐1,4‐dicarboxylic acid (BDC) linkers of UiO‐66 (Figure ) can accelerate the catalytic hydrolysis of DMNP by 20 times compared to the parent UiO‐66 (Figure and Table ) . We originally attributed this activity to synergistic effects between the amine group on the linker and the Zr IV node which could act as a proximal base and Lewis acid, respectively.…”
Section: Figurementioning
confidence: 99%
“…These hazardous materials bind with acetylcholinesterase, an enzyme responsible for destruction of the neurotransmitter acetylcholine via formation of a phosphate ester bond upon exposure. 158,166,168,172 Each of the distinct Zr based SBUs features a classic collection of bridged m 3 -OH groups akin to the PTE active site, which have been anticipated to catalyse the hydrolysis of phosphate esters. 151,152 The embargoed use of some typical CWAs viz.…”
Section: Biomimetic Mofsmentioning
confidence: 99%
“…2.5 mg of MOF powders or 14 mg of MOF-nanofiber kebabs catalyst was dispersed in an aqueous buffer solution of N-ethylmorpholine (0.45 m,p H10), and the degradation kinetics of DMNP were characterized using ap rocedure similar to previous reports. Thea mine moiety in UiO-66-NH 2 is thought to function as aB rønsted base to synergistically enhance the catalytic activity, [30] while the large pore size of UiO-67 may allow faster diffusion and/or more access of DMNP molecules into the active sites of the MOF. UiO-66-NH 2 exhibits the fastest degradation rate (t 1/2 = 2.8 min) among the three MOF powders,w hile UiO-67 also significantly reduces the half-life of DMNP compared to UiO-66.…”
mentioning
confidence: 99%